Potential risks of Artificial Intelligence in education - Zanetti, Margot; Rendina, Stefano; Piceci, Luigi; Peluso Cassese, Francesco (Form@re - Open Journal per la formazione in rete, 2020)
This work analyses the use of Artificial Intelligence (AI) in education from an interdisciplinary point of view and takes into consideration different potential risks. New studies demonstrated that an AI can deviate and become potentially malicious due to various reasons, such as programmers’ biases, corrupted feeds, or purposeful actions therefore it seemed necessary to investigate when and how an AI could deviate in educational environment. The first question to pose is if the risks that an AI presents can be applied also to educative forms of AI. The use (or abuse) of the huge amount of sensitive data that these technologies incorporate is one of the most concerning issues. After a review of the increasing literature that deals with the use of technology in classroom, it can be asserted that there exist certain lacks in this research field, and, eventually, authors formulate concrete questions and suggestions to bridge conceptual gaps. Potenziali rischi dell’Intelligenza Artificiale nell’educazione Questo lavoro analizza l’uso dell’Intelligenza Artificiale (AI) nell’istruzione da un punto di vista interdisciplinare e prende in considerazione diversi potenziali rischi. Nuovi studi hanno dimostrato che un’intelligenza artificiale può deviare e diventare potenzialmente dannosa per vari motivi, come i pregiudizi dei programmatori, i feed corrotti o le azioni intenzionali, pertanto è sembrato necessario indagare quando e come un’AI potrebbe deviare anche in ambito educativo. La prima domanda da porsi è se i rischi che presenta un’AI possono essere applicati anche a forme educative di AI. L’uso (o l’abuso) dell’enorme quantità di dati sensibili che queste tecnologie incorporano è una delle questioni più preoccupanti. Dopo una revisione della crescente letteratura che si occupa dell’uso della tecnologia in classe, si può affermare che esistono alcune carenze in questo campo di ricerca e, infine, gli autori formulano domande e suggerimenti concreti per colmare le lacune concettuali.